Maintaining Maternal–Newborn Safety During the COVID-19 Pandemic - Patrick, Nancy A. (Nurs Womens Health, 2021)
COVID-19, the disease caused by the SARS-CoV-2 virus, was declared a global pandemic by the World Health Organization on March 11, 2020. In addition to older individuals and those with underlying chronic health conditions, maternal and newborn populations were also identified as being at greater risk. It became critical for hospitals and clinicians to maintain the safety of individuals in the facility and minimize the transmission of COVID-19 while continuing to strive for optimized outcomes by providing family-centered care. Rapid change during the pandemic made it appropriate to use the plan–do–study–act (PDSA) cycle to continually evaluate proposed and standard practices. Our team established an obstetric COVID-19 unit for women and newborns, developed guidelines for visitation and for the use of personal protective equipment, initiated universal COVID-19 testing, and provided health education to emphasize shared decision making.